pH levels drive bacterial community structure in sediments of the Qiantang River as determined by 454 pyrosequencing - Liu, Shuai; Ren, Hongxing; Shen, Lidong; Lou, Liping; Tian, Guangming; Zheng, Ping; Hu, Baolan (Frontiers in Microbiology, 2015)
The Qiantang River is a typical freshwater ecosystem that acts as an irreplaceable water source in Zhejiang Province in southeastern China. However, the effects of environmental factors on the bacterial community of this freshwater ecosystem have not been determined. In this study, seven sediment samples were collected along the river. Their bacterial communities were identified using 454 high-throughput sequencing, and the primary environmental factors responsible for shaping the community structure were analyzed. The number of bacterial operational taxonomic units (OTUs) ranged from 2637 to 3933. Using a linear-regression analysis, the OTU numbers were significantly positively correlated with pH (r=0.832, p<0.05) and negatively correlated with nitrate concentration (r=-0.805, p<0.05). A redundancy analysis (RDA) was also performed to test the relationship between the environmental factors and bacterial community composition. The results indicated that pH (p<0.05) and nitrate concentration (p<0.05) were the most significant factors that determined the community distribution of sediment bacteria.